ECOCURE BLUE – NEW COLD BOX SYSTEM WITH ULTRA-HIGH EFFICIENCY AND AS LOW AS POSSIBLE EMISSIONS - P. N. Vacelet; D. Táborský (Литьë и металлургия)
By omitting materials subject to the labeling requirement in part 1 cold-box resin, Düker GmbH from Laufach can achieve an impressive reduction in emissions.Emission and workplace exposure limit values represent major challenges for foundries, and are becoming increasingly important due to every stricter statutory regulations. In particular, compliance with emission guidelines is essential in safeguarding company sites, and is now of equal significance as technical and economic issues. Modern foundries such as Düker GmbH from Laufachpursue a sustainable corporate policy in which the three pillars of cost-effectiveness, social responsibility and environmental protection are accorded equal importance. Düker’s example shows how the use of the new ECOCURE BLUE technology supports environmental protection and occupational health and safety, while also facilitating efficient, highly productive core production.